INOVASI MATERIAL GEOSINTETIK (GEOCELL) DAN KIMIA (GEOPOLL) UNTUK OPTIMALISASI PERBAIKAN JALAN HAULING DI PT. MARUWAI COAL - Raharjo, Oky Fauzi; Mudiyono, Rachmat; Rochim, Abdul (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
PT Maruwai Coal faces challenges in increasing hauling production efficiency due to the decline in the quality of hauling roads. In April 2023, dump truck traffic only reached 1.58 cycles/shift, far below the target of 2 cycles/shift, causing a production loss of 26% (91,280 tons). This condition is influenced by the decline in the quality of hauling roads, which is reflected in the Coal Hauling Road Index (CHRI) value which only reached 81.02% in the 17th week of 2023, far below the standard of 90%. Decreased road performance results in increased travel time, maintenance costs, and faster vehicle damage.   This research aims to apply the principles of geosynthetic (geocell) and chemical (geopoll) materials in improving transport roads. In addition, the Road Maintenance application is used to maintain road conditions, provide recommendations for repairs, and ensure proper implementation of SOPs. A case study was carried out on Segment 4 (KM39”“KM52) by measuring changes in CHRI values, average speed and production results. The application of geocell increased the CHRI value from 83% to 91.23% and extended the life of the road by more than 8 weeks. The use of geopoll increases the bearing capacity of the soil, reduces installation and maintenance costs by 21.95%, and increases the average speed from 35.08 km/h to 38.66 km/h. Production increased from 362,419 tonnes/month to 397,337 tonnes/month, resulting in increased profits of $8,243,790 per month. This research shows that geocells, geopolls and digital applications significantly improve cost efficiency, road performance and support production sustainability at PT Maruwai Coal. This study makes a real contribution to the development of infrastructure technology.